NASKAH PUBLIKASI RENTAL INFORMATION SYSTEM DESIGN WEB BASED ON METRO RANCANG BANGUN SISTEM INFORMASI PENYEWAAN LAPANGAN METRO BERBASIS WEB (Information Technology and Telematics, 2015)
Abstract - Design of information systems leasing Metro Field located in Semarang, precisely at Jl. Agus Salim Imam Bonjol 2-4 Semarang. The old system is applied to the field metro was manual, and often have many constraints faced by them required a long process and complicated. So the system is not running effectively and efficiently. The new system is applied to the field metro is considered to facilitate the performance of employees and customer swhich will facilitate the ground rent is to hire an online field. Leasing in the field metro system is developed using prototyping system using the programming language PHP and MySQL database. The new system is designed to facilitate the management of customer data is renting and leasing transaction datafield. Data collection method used is the field of study that includes observation, interviews with management themetro, as well as literature. Keywords: Rental Information Systems, Metro Square, Prototyping Method, PHP, MySQL.